2008
DOI: 10.1007/s10071-007-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Classification of dog barks: a machine learning approach

Abstract: In this study we analyzed the possible contextspeciWc and individual-speciWc features of dog barks using a new machine-learning algorithm. A pool containing more than 6,000 barks, which were recorded in six diVerent communicative situations was used as the sound sample. The algorithm's task was to learn which acoustic features of the barks, which were recorded in diVerent contexts and from diVerent individuals, could be distinguished from another. The program conducted this task by analyzing barks emitted in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 38 publications
(26 reference statements)
6
56
1
Order By: Relevance
“…However, it was successfully solved for 55.50 % of the bark cases. This is an improvement on the results presented in Molna´r et al (2008), where for six possible contexts the best model yielded a 43 % success rate. With an accuracy rate of 63 % for classifying three possible contexts, our results are similar to the findings reported by Yin and McCowan (2004).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…However, it was successfully solved for 55.50 % of the bark cases. This is an improvement on the results presented in Molna´r et al (2008), where for six possible contexts the best model yielded a 43 % success rate. With an accuracy rate of 63 % for classifying three possible contexts, our results are similar to the findings reported by Yin and McCowan (2004).…”
Section: Discussionsupporting
confidence: 51%
“…Based on the initial parameter set used in Molna´r et al (2008), 29 acoustic measures were extracted from the bark samples with an automated Praat script, see Table 3 and Fig. 1.…”
Section: Sound Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Features such as the ones proposed by Schrader and Hammerschmidt (1997) are all within the reach of feature generation, meaning that the system can find these features or approximations thereof. In fact, feature generation has been shown to outperform approaches based on standard features in the context of animal vocalization (Molnár et al, 2008).…”
Section: B the Feature Generation Approachmentioning
confidence: 99%
“…In an early experiment, Yin and McCowan (2004) found that dog barks could be statistically attributed to individual callers (irrespective of production context) using a discriminant function analysis. Similarly, Molnár et al (2008) developed computer-based learning software, which categorised individual dogs on the basis of their barks. Human listeners, however, struggled to reliability discriminate between barks from dogs of the same breed , although the presentation of five-bark sequences did somewhat improve discrimination.…”
Section: Individual Recognitionmentioning
confidence: 99%